2015
DOI: 10.1039/c4ta06416j
|View full text |Cite
|
Sign up to set email alerts
|

Fast and low temperature growth of electron transport layers for efficient perovskite solar cells

Abstract: We describe a fast, simple and low temperature electrochemical technique for the preparation of zinc oxide layers on rigid and flexible substrates. The layers, prepared from a zinc nitrate precursor, are of high structural and optical quality. They have been optimized to be applied as efficient electron transport layers in CH 3 NH 3 PbI 3 -sensitized perovskite solar cells (PSCs). We show that an electrodeposition time of only two minutes and a low processing temperature are sufficient to fabricate solar cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 38 publications
2
96
0
Order By: Relevance
“…[ 120,[148][149][150][151][152][153][154][155] The Amassian group [ 146 ] employed ZnO nanorods with different aspect ratios, which were also doped with nitrogen. It was found that PSC devices based on such ZnO rods became nearly hysteresis-free with a high PEC of 16.1% (Figure 16 b).…”
Section: Hysteresis-free Pscmentioning
confidence: 99%
“…[ 120,[148][149][150][151][152][153][154][155] The Amassian group [ 146 ] employed ZnO nanorods with different aspect ratios, which were also doped with nitrogen. It was found that PSC devices based on such ZnO rods became nearly hysteresis-free with a high PEC of 16.1% (Figure 16 b).…”
Section: Hysteresis-free Pscmentioning
confidence: 99%
“…29,30 It is therefore a viable alternative to TiO 2 for the PSC application. 13,14,[17][18][19][20][21][22][23][24][25] Kelly et al 20 have reported remarkably high efficiency PSCs using a thin layer of dense planar ZnO prepared by spin-coating. On the other hand, our group has shown that electrodeposition is a promising technique for the low temperature preparation of ZnO ETL for PSC application.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although perovskite (PE) materials are known since the 19 th century, the interest in the use of perovskite as the active light absorbing material in a solar cell is much more recent. Methylammonium lead halide compounds were used for the first time as a sensitizer in a liquid-electrolyte analog of a DSSC in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] To boost the PCEs, both the hole extraction layer (HEL) and electron extraction layer (EEL) are employed in pero-HSCs to sufficiently and effectively extract and transport the charge carriers from the perovskite light-harvester layer to the corresponding electrodes. [4][5][6][7][8] For example, in the planner heterojunction (PHJ) pero-HSCs with a device structure of ITO/PEDOT:PSS/ perovskite/PC 61 BM/Al, where ITO is indium tin oxide as the anode, Al is aluminum as the cathode, PEDOT:PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) and PC 61 BM (phenyl-C 61 -butyric acid methyl ester) are applied as the HEL and EEL, respectively, to boost the PCEs. [9][10][11][12] In order to further boost the PCEs of the PHJ pero-HSCs, one ongoing focus is the interfacial engineering of the PC 61 BM EEL to manipulate the electron extraction, transport, and collection processes from the perovskite layer to the cathode.…”
mentioning
confidence: 99%